PEMERIKSAAN GOLONGAN DARAH SISTEM ABO RHESUS PADA MAHASISWA STIKES RAJEKWESI BOJONEGORO - Fatia Rizki Nuraini; Nina Difla Muflikhah; Siti Nurkasanah (Jurnal Abdi Insani, 2022)
Blood Type is an important thing to every person to understand and can identify using a specific methods, blood typing. Blood typing refers to a specific pattern of reaction to testing antisera within a given system. Blood typing have several methods, the common method that usually used is Direct Slide Test. Over a period of time, our understanding on blood groups has evolved to encompass not only transfusion-related problems but also specific disease association with RBC surface antigens. This community service activity aimed to provide blood typing examination for students who unknown their blood type and strenghten the understanding about the important of Blood Type. This activity was held on December 20, 2021 in Stikes Rajekwesi Bojonegoro. This Community service applied an examination test to several students who still unknown their blood type. Examination of blood group used the A-B-O system and rhesus with the slide test method. The results of the blood group examination of 16 students showed that the highest results were blood group B as many as 6 people (37.5%) and the least blood group being O and AB with 3 people each (18.75). Rhesus examination showed that all students were rhesus positive (100%). Students who examinated during the programmes doesn’t have undestanding of the important of knowing their blood type. Students of Stikes Rajekwesi Bojonegoro get sufficient understanding about the important of knowing their blood type and the blood typing showed 37,5% of student are B type, 18,75% are O and AB type each, while 100% rhesus positive.